2017
DOI: 10.2196/cardio.7848
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Health Intervention to Improve Self-Care in Patients With Heart Failure: Pilot Randomized Control Trial

Abstract: BackgroundHeart failure (HF) is a progressive chronic disease affecting 6.5 million Americans and over 15 million individuals globally. Patients with HF are required to engage in complex self-care behaviors. Although the advancements in medicine have enabled people with HF to live longer, they often have poor health-related quality of life and experience severe and frequent symptoms that limit several aspects of their lives. Mobile phone apps have not only created new and interactive ways of communication betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
126
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(151 citation statements)
references
References 60 publications
0
126
0
3
Order By: Relevance
“…Ten of the 18 studies included in this review had small sample sizes of 40 or fewer participants (8 studies assessed usability of the mobile system for refinement or further development of an algorithm [31-40]), 4 studies had sample sizes of 41 to 99 [41-44], and 4 studies had 100 or more participants (but fewer than 200) [45-48]. Four of the 18 studies reviewed were pilot RCTs [32,34,42,44], and only 2 RCTs had 100 or more participants [47,48]. Total sample from all 18 studies was 847 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten of the 18 studies included in this review had small sample sizes of 40 or fewer participants (8 studies assessed usability of the mobile system for refinement or further development of an algorithm [31-40]), 4 studies had sample sizes of 41 to 99 [41-44], and 4 studies had 100 or more participants (but fewer than 200) [45-48]. Four of the 18 studies reviewed were pilot RCTs [32,34,42,44], and only 2 RCTs had 100 or more participants [47,48]. Total sample from all 18 studies was 847 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a usability study among minorities in the VA population (n=61) reported moderate program satisfaction scores (mean 6.84 [SD 0.46]) and improved self-efficacy and quality of life [42]. Another comprehensive app established usability and improved self-management and quality of life in a pilot RCT [10,32]. Providing HF education via MP3 player showed reduced readmission rates [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CVD counteractive action measures are perceived as a basic focus by social insurance associations around the world. [4]. L.Sathish Kumar and A. Padmapriya has given a paper named Prediction for similarities of disease by using ID3 algorithm in television and mobile phone.…”
Section: Introductionmentioning
confidence: 99%
“…diagnosed with this condition to enjoy an improved quality of life [8,9]. Accordingly, digital health interventions have recently been developed to simplify the process of managing and tracking the symptoms of HF [10][11][12][13][14][15][16][17][18][19]. One such intervention, which was developed alongside HF patients and clinicians living in Canada, has been shown to improve patient self-care and quality of life amongst Canadian HF patients [19,20].…”
mentioning
confidence: 99%